Exploring the Potential Effect of Phospholipase A2 Antibody to Extend Beef Shelf-Life in a Beef Liposome Model System - C. K. Chun; R. Welti; M. Roth; M. P. Richards; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this study was to utilize a beef liposome model system to investigate if phospholipase-A2antibody (aPLA2) can be used to inhibit phospholipase-A2(PLA2) activity to potentially improve beef shelf-life. Study Description:Phospholipids (PL) from 10 U.S. Department of Agriculture choice beef striploin steaks were extracted and split into six treatments: PL (25 mg of PL); aPLA10 (PL + 25 µg of aPLA2); aPLA20 (PL + 50 µg of aPLA2); PLA2 (PL + 10 µg of PLA2); PLA2+aPLA10 (PL + PLA2 + aPLA10); and PLA2+aPLA20 (PL + PLA2 + aPLA20). The model system was under retail display at 39°F and 2300 lux for 7 days. At day 0, aliquots were taken for PL profiling and product ion analysis. At days 0, 1, 4, and 7, aliquots were taken for lipid oxidation analysis. Results:At day 7 of display, PLA2, PLA2+aPLA10, and PLA2+aPLA20 treatments had greater lipid oxidation (P<0.01) compared to the samples without PLA2. This trend was seen in the other retail display periods. Interestingly, day-7 aPLA10 and aPLA20 had less lipid oxidation than day-7 PL and less oxidation than day-4 PLA2 (P<0.05). The PL profile analysis showed clear differences between treatments with or without the addition of PLA2. The PLA2 treatments showed greater relative percent of total PL degradation products (P<0.01) than treatments without PLA2. The PLA2 treatments had less relative percent of total ether-linked phosphatidylcholine (ePC) than treatments without PLA2 (P<0.01). It appears that aPLA2 had no effect on inhibiting PLA2 hydrolysis as there was no difference (P>0.10) between PLA2 and aPLA+PLA2 treatments in relative percent of total ePC, phosphatidylcholine (PC), or in PL degradation products. The Bottom Line:Phospholipase-A2significantly alters beef phospholipids to a composition that is potentially susceptible to lipid oxidation. At day-7 of retail display, there is significant lipid oxidation from PLA2 added treatments, yet the aPLA2 only treatments seem to present an antioxidant effect. Effectively inhibiting PLA2 activity can potentially improve beef shelf-life stability.
Keywords: phospholipase-A2; phospholipid; lipid oxidation